Living under occupation: Palestinian teachers' experiences and their digital responses - John Traxler; Zuheir Khaif; Alan Nevill; Saida Affouneh; Soheil Salha; Ali Zuhd; Fuad Trayek (Association for Learning Technology, 2019)
Unlike most neighbouring countries in the world, teachers in the occupied territories of Palestine face extraordinary conditions and challenges. These are due to the continued Israeli occupation. This article reports on a large-scale survey of Palestinian teachers. It explores the impact of the occupation on the professional lives of the teachers around Nablus, and indirectly on their students and communities, and on their digital responses. Follow-up focus groups explore their feelings, experiences and reactions, providing greater insights into this complex and troubling situation. The article underpins further work on appropriate digital literacy. It does however also provide an insight into the challenges to rigorous fieldwork outside the mainstream of the developed North and specifically in a region of conflict and occupation.